Management and Clinical Outcomes of 37 Patients with Necrotizing Otitis Externa: Retrospective Review of a Standardized 6-Week Treatment Pathway - Dhariwal, Ankush; Manjaly, Joseph G; Patel, Bhavesh; Morris-Jones, Stephen; David, Kate; Khetarpal, Priya; Beale, Tim; Mehta, Nishchay; Logan, Sarah (Journal of International Advanced Otology, 2023)
BACKGROUND: Necrotizing otitis externa is an invasive infection, affecting older patients, with significant associated morbidity. Despite this, there are no randomized controlled trials that address management, and therefore, treatment approaches may vary considerably. We describe the management and outcomes of 37 patients managed using a multidisciplinary treatment pathway for necrotizing otitis externa over a 5-year period. The pathway is based on a standardized antibiotic regime of 3 weeks of intravenous ceftazidime plus oral ciprofloxacin, followed by a further 3 weeks of ciprofloxacin. METHODS: This is a retrospective review of all patients diagnosed with necrotizing otitis externa since the introduction of our pathway in 2016. We include data on patient demographics, comorbidities, microbiology, length of stay, and length of antimicrobial treatment. Outcome data, including mortality, relapse and treatment failure, and adverse effects of treatment, are presented. RESULTS: The median age of our patients was 82 years. About 54% of patients had diabetes mellitus or another cause of immunocompromise. Pseudomonas aeruginosa was isolated in 68%. The median duration of inpatient stay was 9 days, and median treatment duration was 6 weeks. Of 37 patients, 32 were cured (86%), and of the remaining 5 patients, there were 2 mortalities unrelated to necrotizing otitis externa and 3 patients with recurrent infections due to anatomical abnormalities. CONCLUSION: We note favorable treatment outcomes when using a standardized multidisciplinary pathway and a 6-week course of antibiotic therapy. Cite this article as: Dhariwal A, Manjaly JG, Patel B, et  al. Management and clinical outcomes of 37 patients with necrotizing otitis externa: retrospective review of a standardized 6-week treatment pathway. J Int Adv Otol. 2023;19(3):223-227.